Positive buck-boost converter - Hong, Zu Xin. (2009)
Through the increasing advancement in technologies, more devices are designed with better efficiency and additional functionality. With the increasing demand for low-voltage devices, superior and efficient power management techniques are entrenched into these devices. The most common choice of voltage source for these devices is the Li-ion battery. A single Li-ion battery voltage output ranges from 4.2V to 2.7V.